Serotonergic projections from the raphe nuclei to the subthalamic nucleus; a retrograde- and anterograde neuronal tracing study. (26th January 2016) - Reznitsky, Martin; Plenge, Per; Hay-Schmidt, Anders
Highlights: 5-HT is important in movement control. Serotonergic projections to the STN from the DRN have not been thoroughly described. All STN afferents from the raphe system projects from the DRN, mainly DRD and DRL. Approximately 34% of the STN afferents from the DRN are serotonergic. Abstract: The objective of this study is to establish which subdivision of the dorsal raphe nucleus (DRN) supplies serotonergic projections to the subthalamic nucleus (STN) in the rat brain. Several studies in recent years have shown that serotonin (5-HT) might have a therapeutic role in the most prevalent basal ganglia (BG) movement disorder, Parkinson's disease (PD), but, because of the depletion of dopaminergic input to the BG, l -DOPA has been the main treatment for PD patients. Autoradiography showed that serotonin receptors 5-HT1B and 5-HT2C and the serotonin transporter were present in STN, whereas the 5-HT1A and 5-HT2A not were present. Retrograde tracer FluoroGold or Choleratoxin subunit B were iontophoretically delivered in the STN and combined with immunohistochemistry for 5-HT in order to map the topographic organization in the dorsal raphe system. The study showed that approximately 320+/−137 neurons were retrogradely traced from each STN to the DRN, located mainly in the dorsal- and ventrolateral DRN, and of these 108+/−42 or 34% co-localized 5-HT. Additionally anterograde tracer PHA-L was injected in the DRN to confirm projections to STN and accordingly only a sparse number of axon terminals were observed in the STN.